Phase shift mask blank, phase shift mask, and method for manufacturing a phase shift mask

CN116018556BActive Publication Date: 2026-10-16KASEI TOKUKO MODEL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180054819.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-08
Filing Date
2021-09-07
Publication Date
2026-10-16
Estimated Expiration
2041-09-07

AI Technical Summary

Technical Problem

[0007]然而,在专利文献1、2所记载的技术中,存在着抑制上述那样的雾度的效果不充分的情况

Benefits of technology

[0019] By using the phase-shift mask blank according to one aspect of the present invention, the generation of haze on the mask can be sufficiently suppressed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116018556B_ABST
    Figure CN116018556B_ABST
Patent Text Reader

Abstract

Provided are a phase shift mask blank capable of sufficiently suppressing generation of haze on a mask, a phase shift mask having few haze defects, and a manufacturing method of the phase shift mask. The phase shift mask blank (10) according to the present embodiment is a phase shift mask blank for manufacturing a phase shift mask suitable for exposure light having a wavelength of 200 nm or less, and includes a substrate (11) and a phase shift film (14) formed on the substrate (11). The phase shift film (14) includes a phase layer (12) capable of adjusting a predetermined amount of phase and transmittance individually with respect to the transmitted exposure light, and a protective layer (13) formed on the phase layer (12) and preventing gas from permeating the phase layer (12). When the film thickness of the phase layer (12) is d1 and the film thickness of the protective layer (13) is d2, the film thickness (d1) of the phase layer (12) is thicker than the film thickness (d2) of the protective layer (13), and the film thickness (d2) of the protective layer (13) is 15 nm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a phase shift mask blank, a phase shift mask, and a method for manufacturing a phase shift mask used in the manufacture of semiconductor devices and the like. Background Technology

[0002] In recent years, semiconductor processing, especially due to the high integration of large-scale integrated circuits, has required miniaturization of circuit patterns, leading to increasingly stringent requirements for the miniaturization of wiring patterns and contact hole patterns that constitute circuits. Therefore, the exposure light sources used in the manufacture of semiconductor devices have evolved from KrF excimer lasers (wavelength 248nm) to shorter wavelength ArF excimer lasers (wavelength 193nm).

[0003] In addition, phase-shift masks are used to improve wafer transfer characteristics. In a phase-shift mask, both the phase difference and transmittance can be adjusted so that the phase difference (hereinafter referred to as "phase difference") between the ArF excimer laser light transmitted through the transparent substrate and the ArF excimer laser light transmitted through both the transparent substrate and the phase-shift film is 180 degrees, and the ratio (hereinafter referred to as "transmittance") of the amount of ArF excimer laser light transmitted through the transparent substrate to the amount of ArF excimer laser light transmitted through the phase-shift film is 6%.

[0004] For example, there is a known method where, in the case of fabricating a phase-shifting mask with a phase difference of 180 degrees, the thickness of the phase-shifting film is set so that the phase difference is around 177 degrees, and then the transparent substrate is processed to about 3 nm while the phase-shifting film is dry-etched using fluorine gas, and finally the phase difference is adjusted to around 180 degrees.

[0005] In phase-shift masks suitable for exposure light with wavelengths below 200 nm, foreign matter, sometimes referred to as "haze," gradually forms / grows / appears on the mask due to exposure, rendering the mask unusable. In particular, when the phase-shift film is composed of light elements such as silicon, transition metals, oxygen, or nitrogen, foreign matter may sometimes form on the surface of the phase-shift film.

[0006] As a technology for suppressing haze, there are, for example, the technologies described in Patent Documents 1 and 2.

[0007] However, the technologies described in Patent Documents 1 and 2 are not sufficiently effective in suppressing the aforementioned haze.

[0008] Existing technical documents

[0009] Patent documents

[0010] Patent Document 1: Japanese Patent Application Publication No. 2018-173621

[0011] Patent Document 2: Japanese Patent No. 4579728 Summary of the Invention

[0012] The problem to be solved by the present invention

[0013] The present invention was made based on the above circumstances, and its purpose is to provide a phase shift mask blank that can sufficiently suppress the generation of haze on the surface of a phase shift film, a phase shift mask with few haze defects, and a method for manufacturing the phase shift mask.

[0014] Solution for solving the problem

[0015] This invention was made to solve the aforementioned problems. One aspect of this invention relates to a phase-shifting mask preform for fabricating a phase-shifting mask suitable for exposure light with wavelengths below 200 nm. The preform is characterized by comprising a transparent substrate and a phase-shifting film formed on the transparent substrate. The phase-shifting film comprises: a phase difference transmittance adjustment layer capable of adjusting the phase and transmittance of the transmitted exposure light by predetermined amounts; and a gas permeability protection layer formed on the phase difference transmittance adjustment layer to prevent gas from permeating into the phase difference transmittance adjustment layer. The phase difference transmittance adjustment layer is located on the transparent substrate side. When the thickness of the phase difference transmittance adjustment layer is set to d1 and the thickness of the gas permeability protection layer is set to d2, d1 is greater than d2, and d2 is less than 15 nm.

[0016] In addition, one aspect of the present invention relates to a phase-shifting mask suitable for exposure light with wavelengths below 200 nm, a phase-shifting mask having a circuit pattern, characterized in that it comprises a transparent substrate and a phase-shifting film formed on the transparent substrate, the phase-shifting film comprising: a phase difference transmittance adjustment layer capable of adjusting the phase and transmittance of the transmitted exposure light by a predetermined amount respectively; and a gas permeability protection layer formed on the phase difference transmittance adjustment layer to prevent gas from passing through the phase difference transmittance adjustment layer, the phase difference transmittance adjustment layer being located on the transparent substrate side, wherein when the film thickness of the phase difference transmittance adjustment layer is set to d1 and the film thickness of the gas permeability protection layer is set to d2, d1 is greater than d2, and d2 is less than 15 nm.

[0017] Furthermore, one aspect of the present invention relates to a method for manufacturing a phase shift mask using the aforementioned phase shift mask blank, characterized by comprising: a step of forming a light-shielding film on the phase shift film; a step of forming a resist pattern on the light-shielding film formed on the phase shift film; a step of forming a pattern on the light-shielding film by oxychlorine-based etching (Cl / O-based) after forming the resist pattern; a step of forming a pattern on the phase shift film by fluorine-based etching (F-based) after forming the pattern on the light-shielding film; a step of removing the resist pattern after forming the pattern on the phase shift film; and a step of removing the light-shielding film from the phase shift film by oxychlorine-based etching (Cl / O-based) after removing the resist pattern.

[0018] The effects of the invention

[0019] By using the phase-shift mask blank according to one aspect of the present invention, the generation of haze on the mask can be sufficiently suppressed. Attached Figure Description

[0020] [ Figure 1 This is a cross-sectional schematic diagram illustrating the structure of a phase-shifting mask blank according to an embodiment of the present invention.

[0021] [ Figure 2 This is a cross-sectional schematic diagram illustrating the configuration of a phase-shifting mask according to an embodiment of the present invention.

[0022] [ Figure 3 This is a cross-sectional schematic diagram illustrating the manufacturing process of a phase shift mask using a phase shift mask blank according to an embodiment of the present invention. Detailed Implementation

[0023] The inventors of this application believe that if the three elements of the phase adjustment film (the phase difference transmittance adjustment layer described later) constituting the phase-shifting mask blank or the phase-shifting mask—the constituent material, oxidizing gases such as water or oxygen, and exposure energy—are not all present, then the generation of haze in the mask blank or the mask can be reduced. Therefore, the phase-shifting mask blank or the phase-shifting mask is configured as follows. That is, the phase-shifting mask blank, the phase-shifting mask, and the manufacturing method thereof involved in this embodiment are based on the following technical concept: by providing a gas protection layer (so-called gas barrier layer) on the phase adjustment film, the oxidizing gas is prevented from contacting the constituent material of the phase adjustment film, thereby reducing the generation of haze.

[0024] Hereinafter, the method for carrying out the present invention will be described with reference to the accompanying drawings. It should be noted that the cross-sectional schematic diagram does not accurately reflect the actual size ratio and number of patterns, as the amount of tunneling of the transparent substrate and the amount of damage to the film are omitted.

[0025] As a preferred embodiment of the phase-shifting mask blank of the present invention, the following methods can be listed.

[0026] (Overall structure of the phase-shifting mask blank)

[0027] Figure 1 A cross-sectional schematic diagram illustrating the structure of a phase-shifting mask blank according to an embodiment of the present invention. Figure 1 The phase-shift mask blank 10 shown is a phase-shift mask blank used to fabricate a phase-shift mask suitable for exposure light with a wavelength of 200 nm or less. It includes: a substrate (hereinafter, simply referred to as "substrate") 11 that is transparent to the exposure wavelength and a phase-shift film 14 formed on the substrate 11. The phase-shift film 14 includes at least: a phase difference transmittance adjustment layer (hereinafter, simply referred to as "phase layer") 12 that can adjust the phase and transmittance of the transmitted exposure light by predetermined amounts; and a gas permeability protection layer (hereinafter, simply referred to as "protective layer") 13 formed on the phase difference transmittance adjustment layer 12 to prevent gas from passing through the phase difference transmittance adjustment layer 12. The phase layer 12 is located on the substrate 11 side. Furthermore, when the thickness of the phase layer 12 is set to d1 and the thickness of the protective layer 13 is set to d2, d1 is greater than d2, and d2 is 15 nm or less.

[0028] The following describes in detail each layer of the phase-shifting mask blank 10 according to the embodiments of the present invention.

[0029] (Substrate)

[0030] There are no particular restrictions on the substrate 11. For example, quartz glass, CaF2 or aluminum silicate glass are commonly used as the substrate 11.

[0031] (Phase-shifting film)

[0032] The phase shift film 14 comprises a phase layer 12 and a protective layer 13 in sequence, and is formed on the substrate 11 with or without other films.

[0033] The phase-shifting film 14 is, for example, a film that is resistant to oxychlorine-based etching (Cl / O-based) and can be etched by fluorine-based etching (F-based).

[0034] The transmittance of the phase-shifting film 14 relative to the transmittance of the substrate 11 is, for example, in the range of 3% to 80%, and the optimal transmittance can be appropriately selected according to the desired wafer pattern. Furthermore, the phase difference of the phase-shifting film 14 is, for example, in the range of 160 degrees to 220 degrees, and more preferably in the range of 175 degrees to 190 degrees. That is, the transmittance of the phase-shifting film 14 to the exposure light can be in the range of 3% to 80%, and the phase difference can be in the range of 160 degrees to 220 degrees. If the transmittance of the phase-shifting film 14 to the exposure light is less than 3%, good exposure performance may not be obtained. Conversely, if the phase difference is in the range of 160 degrees to 220 degrees, the desired exposure performance can be easily maintained.

[0035] <Phase Layer>

[0036] Phase layer 12 is a layer formed on substrate 11 with or without other films, capable of adjusting the phase and transmittance of transmitted exposure light by predetermined amounts. Here, "adjusting phase" means (for example) reversing the phase. "Transmittance" refers to the transmittance of exposure light.

[0037] The phase layer 12 is, for example, a single-layer film containing silicon and at least one of transition metals, nitrogen, oxygen, and carbon, or a multilayer film or tilted film thereof, and the transmittance and phase difference relative to the exposure wavelength are adjusted by appropriately selecting the composition and film thickness.

[0038] Regarding phase layer 12, in the overall elemental composition of phase layer 12, it is preferable to contain silicon in the range of 20 atomic% to 60 atomic%; preferably, to contain transition metal in the range of 0 atomic% to 20 atomic%; preferably, to contain nitrogen in the range of 30 atomic% to 80 atomic%; preferably, to contain oxygen in the range of 0 atomic% to 30 atomic%; and preferably, to contain carbon in the range of 0 atomic% to 10 atomic%. Regarding more preferred content ranges for each element in phase layer 12, in the overall elemental composition of phase layer 12, silicon is in the range of 30 atomic% to 50 atomic%; transition metal is in the range of 0 atomic% to 10 atomic%; nitrogen is in the range of 40 atomic% to 70 atomic%; oxygen is in the range of 0 atomic% to 20 atomic%; and carbon is in the range of 0 atomic% to 5 atomic%. If the content of each element in phase layer 12 is within the above-mentioned numerical ranges, the transmittance and phase difference of phase layer 12 can be easily controlled.

[0039] It should be noted that the phase layer 12 may also contain at least one of the oxides, carbides, and nitrides of metal silicides. In this case, the metal constituting the metal silicide may also be the aforementioned transition metal.

[0040] The transition metal contained in the phase layer 12 is preferably selected from at least one of molybdenum, titanium, vanadium, cobalt, nickel, zirconium, niobium, and hafnium, and is more preferably molybdenum. If the transition metal contained in the phase layer 12 is selected from at least one of molybdenum, titanium, vanadium, cobalt, nickel, zirconium, niobium, and hafnium, the processing of the phase layer 12 becomes easier, and if it is molybdenum, the processability of the phase layer 12, such as etching, is further improved.

[0041] When the thickness of the phase layer 12 is set to d1 and the thickness of the protective layer 13 is set to d2, the thickness d1 of the phase layer 12 is thicker than the thickness d2 of the protective layer 13, and the thickness d2 of the protective layer 13 is less than 15 nm. It should be noted that when the thickness d2 of the protective layer 13 is thicker than 15 nm, the optical and correction properties may be affected.

[0042] Furthermore, the film thickness d1 of the phase layer 12 can be thicker than 15 nm. When the film thickness d1 of the phase layer 12 is thicker than 15 nm, it becomes easier to adjust the phase and transmittance.

[0043] Furthermore, it is preferable if the combined thickness of the phase layer 12 and the protective layer 13 is 50 nm or more; it is more preferable if it is 70 nm or more. If the combined thickness of the phase layer 12 and the protective layer 13 is within the above-mentioned range, it is easy to set the function of the phase shift film 14 to the desired value.

[0044] <Protective Layer>

[0045] The protective layer 13 is a layer formed on the phase layer 12, with or without other films, to prevent / suppress the permeation of gases into the phase layer 12 (especially the permeation of oxidizing gases such as water and oxygen), i.e., a gas barrier layer. According to this embodiment, the intrusion of gases considered to be one of the factors of haze generation into the phase layer 12 can be prevented / suppressed, thus even under conditions of prolonged mask use (e.g., when the dose on the mask exceeds 100 kJ / cm²). 2 In certain situations, it can also prevent / suppress the generation of haze on the surface of the phase-shift mask.

[0046] It should be noted that the gas (atmosphere gas) that is blocked / suppressed from passing through by the protective layer 13 is an oxidizing gas, specifically oxygen-containing molecules, and more specifically water molecules.

[0047] The protective layer 13 is preferably a layer that is resistant to etching by oxychlorine-based (Cl / O-based) gases, can be etched by fluorine-based gases (F-based), and can be corrected by EB (electron beam) correction method.

[0048] The protective layer 13 is preferably a single-layer film, a mixed film of these compounds, or a multilayer film composed of one or more compounds selected from tantalum metal, tantalum compound, tungsten metal, tungsten compound, tellurium metal, and tellurium compound. However, as long as it is a barrier layer, the composition is not particularly limited. It should be noted that the aforementioned tantalum metal, tungsten metal, and tellurium metal refer to the elemental form of each metal.

[0049] The protective layer 13, which is composed of tantalum compounds, is a single-layer film containing tantalum and one or more elements selected from oxygen, nitrogen and carbon, or a multilayer film or a tilted film thereof.

[0050] Regarding the protective layer 13 composed of tantalum compound, it is preferable that the elemental composition of the protective layer 13 contains tantalum in the range of 10 atomic% to 90 atomic%; oxygen in the range of 0 atomic% to 90 atomic%; nitrogen in the range of 0 atomic% to 70 atomic%; and carbon in the range of 0 atomic% to 20 atomic% throughout the protective layer 13. More preferably, in the elemental composition of the protective layer 13, tantalum is in the range of 20 atomic% to 80 atomic%; oxygen is in the range of 0 atomic% to 80 atomic%; nitrogen is in the range of 0 atomic% to 60 atomic%; and carbon is in the range of 0 atomic% to 10 atomic% throughout the protective layer 13. If the content of each element in the protective layer 13 composed of tantalum compound is within the above-mentioned numerical range, the performance of the protective layer 13 in preventing gas permeation to the phase layer 12 is improved.

[0051] In addition, the protective layer 13, which is composed of tungsten compounds, is a single-layer film containing tungsten and one or more elements selected from oxygen, nitrogen and carbon, or a multilayer film or a tilted film thereof.

[0052] Regarding the protective layer 13 composed of tungsten compounds, it is preferable that the elemental composition of the protective layer 13 contains tungsten in the range of 10 atomic% to 70 atomic%; oxygen in the range of 30 atomic% to 90 atomic%; nitrogen in the range of 0 atomic% to 20 atomic%; and carbon in the range of 0 atomic% to 20 atomic% throughout the entire protective layer 13. More preferably, in the elemental composition of the protective layer 13 composed of tungsten compounds, tungsten is in the range of 20 atomic% to 60 atomic%; oxygen is in the range of 50 atomic% to 80 atomic%; nitrogen is in the range of 0 atomic% to 10 atomic%; and carbon is in the range of 0 atomic% to 10 atomic% throughout the entire protective layer 13. If the content of each element in the protective layer 13 composed of tungsten compounds is within the above-mentioned numerical ranges, the performance of the protective layer 13 in preventing gas permeation to the phase layer 12 is improved.

[0053] In addition, the protective layer 13 composed of tellurium compounds is a single-layer film containing tellurium and one or more elements selected from oxygen, nitrogen and carbon, or a multilayer film or a tilted film thereof.

[0054] Regarding the protective layer 13 composed of tellurium compounds, the elemental composition of the protective layer 13 preferably contains tellurium in the range of 20 atomic% to 70 atomic%; oxygen in the range of 30 atomic% to 90 atomic%; nitrogen in the range of 0 atomic% to 20 atomic%; and carbon in the range of 0 atomic% to 20 atomic%. More preferably, in the elemental composition of the protective layer 13 composed of tellurium compounds, tellurium is in the range of 30 atomic% to 60 atomic%; oxygen is in the range of 50 atomic% to 80 atomic%; nitrogen is in the range of 0 atomic% to 10 atomic%; and carbon is in the range of 0 atomic% to 10 atomic%. If the content of each element in the protective layer 13 composed of tellurium compounds is within the above-mentioned numerical ranges, the performance of the protective layer 13 in preventing gas permeation to the phase layer 12 is improved.

[0055] As described above, if the protective layer 13 is a single-layer film, a mixed film of these compounds, or a multilayer film composed of one or more compounds selected from tantalum metal, tantalum compound, tungsten metal, tungsten compound, tellurium metal, and tellurium compound, it can effectively prevent gas from permeating into the phase layer 12.

[0056] It should be noted that the film thickness d2 of the protective layer 13 is less than 15 nm as described above. If the film thickness d2 of the protective layer 13 is within the above-mentioned range, the optical properties and correction properties can be maintained, and the performance of blocking gas from passing through the phase layer 12 can also be maintained.

[0057] (Overall structure of phase-shifting masks)

[0058] The configuration of the phase shift mask 100 according to the embodiments of the present invention will be described below.

[0059] Figure 2 A cross-sectional schematic diagram illustrating the configuration of a phase-shifting mask according to an embodiment of the present invention. Figure 2The phase-shift mask 100 shown is a patterned phase-shift mask (i.e., a patterned phase-shift mask) suitable for exposure light with wavelengths of 200 nm or less. It comprises a substrate 11 that is transparent to the exposure wavelength and a phase-shift film 14 formed on the substrate 11. The phase-shift film 14 includes at least a phase layer 12 capable of adjusting the phase and transmittance of the transmitted exposure light by predetermined amounts, and a protective layer 13 formed on the phase layer 12 to prevent gas from passing through it. The phase layer 12 is located on the substrate 11 side. Furthermore, when the thickness of the phase layer 12 is set to d1 and the thickness of the protective layer 13 is set to d2, d1 is greater than d2, and d2 is 15 nm or less.

[0060] The phase shift mask 100 has a phase shift film pattern 17 formed by removing a portion of the phase shift film 14 and exposing the surface of the substrate 11.

[0061] It should be noted that the composition of each layer of the phase shift mask 100 constituting the embodiment of the present invention is the same as the composition of each layer of the phase shift mask blank 10 constituting the embodiment of the present invention described above, therefore, detailed descriptions of the composition of each layer are omitted.

[0062] (Manufacturing method of phase-shifting mask blank)

[0063] The manufacturing method of the phase shift mask 100 using the phase shift mask blank 10 according to this embodiment includes: a step of forming a light-shielding film 15 on a phase shift film 14; a step of forming a resist pattern 16 on the light-shielding film 15 formed on the phase shift film 14; a step of forming a pattern on the light-shielding film 15 by oxychlorine-based etching (Cl / O-based) after forming the resist pattern 16; a step of forming a pattern on the phase shift film 14 by fluorine-based etching (F-based) after forming the pattern on the phase shift film 14; a step of removing the resist pattern 16 after forming the pattern on the phase shift film 14; and a step of removing the light-shielding film 15 from the phase shift film 14 by oxychlorine-based etching (Cl / O-based) after removing the resist pattern 16.

[0064] Here, the light-shielding film 15 according to the embodiments of the present invention will be described.

[0065] <Light-shielding film>

[0066] The light-shielding film 15 is a layer formed on the phase-shifting mask blank 10 (protective layer 13) according to the above-described embodiment of the present invention.

[0067] The light-shielding film 15 is, for example, a single-layer film, a multilayer film, or a tilted film made of elemental chromium or chromium compounds. More specifically, the light-shielding film 15 made of chromium compounds is a single-layer film, a multilayer film, or a tilted film containing chromium and one or more elements selected from nitrogen and oxygen.

[0068] Regarding the light-shielding film 15 composed of chromium compounds, it is preferable that the film contains chromium in the range of 30 atomic% to 100 atomic% of its total elemental composition, oxygen in the range of 0 atomic% to 50 atomic% of its total elemental composition, nitrogen in the range of 0 atomic% to 50 atomic% of its total elemental composition, and carbon in the range of 0 atomic% to 10 atomic% of its total elemental composition. More preferably, in the light-shielding film 15 composed of chromium compounds, chromium is in the range of 50 atomic% to 100 atomic% of its total elemental composition, oxygen is in the range of 0 atomic% to 40 atomic% of its total elemental composition, nitrogen is in the range of 0 atomic% to 40 atomic% of its total elemental composition, and carbon is in the range of 0 atomic% to 5 atomic% of its total elemental composition. If the content of each element in the light-shielding film 15 composed of chromium compounds is within the above-mentioned numerical range, the light-shielding properties of the film 15 are improved.

[0069] The thickness of the light-shielding film 15 is preferably in the range of 35 nm to 80 nm, and particularly preferably in the range of 40 nm to 75 nm.

[0070] The light-shielding film 15 can be formed by known methods. Sputtering is the preferred method for obtaining a film with excellent homogeneity, but this embodiment is not limited to sputtering.

[0071] The target material and sputtering gas are selected based on the film composition. For example, as a film deposition method for chromium-containing films, the following methods can be listed: using a chromium-containing target material, reactive sputtering is performed only in an inert gas such as argon, only in a reactive gas such as oxygen, or in a mixture of inert and reactive gases. The flow rate of the sputtering gas can be adjusted according to the film characteristics and can be constant during film deposition. When it is desired to vary the oxygen and nitrogen content along the thickness direction of the film, it can be varied according to the target composition. In addition, the applied power to the target material, the distance between the target material and the substrate, and the pressure in the film deposition chamber can also be adjusted.

[0072] Hereinafter, the steps of the manufacturing method of the phase shift mask 100 according to the embodiments of the present invention will be described in detail.

[0073] Figure 3 To show the use of Figure 1 A cross-sectional schematic diagram of the manufacturing process of the phase shift mask 100 of the phase shift mask blank 10 shown. Figure 3 (a) shows the process of forming a light-shielding film 15 on the phase-shifting film 14. Figure 3 (b) shows the process of coating a resist film on a light-shielding film 15, performing a drawing, and then performing a development process to form a resist pattern 16. Figure 3(c) illustrates the process of patterning the light-shielding film 15 along the resist pattern 16 by oxygen-chlorine dry etching (Cl / O system). Figure 3 (d) illustrates the process of patterning the phase shift film 14 along the pattern of the light-shielding film 15 by fluorine-based etching (F-based) to form the phase shift film pattern 17. Figure 3 (e) illustrates the cleaning process after the resist pattern 16 has been stripped away. Figure 3 (f) illustrates the process of removing the light-shielding film 15 from the phase shift film 14 on which the phase shift film pattern 17 is formed by an oxygen-chlorine based etching method (Cl / O based). This is how the phase shift mask 100 according to this embodiment is manufactured.

[0074] The phase-shifting mask 100 according to this embodiment is a phase-shifting mask suitable for exposure light with a wavelength of 200 nm or less, and includes: a substrate 11, and a phase-shifting film 14 formed on the substrate 11 with or without other films. The phase-shifting film 14 includes: a phase layer 12 capable of adjusting the phase and transmittance of the transmitted exposure light by predetermined amounts; and a protective layer 13 formed on the phase layer 12 to prevent gas from passing through the phase layer 12, the phase layer 12 being located on the substrate 11 side. Furthermore, the phase-shifting mask 100 includes a phase-shifting film pattern 17 formed by removing a portion of the phase-shifting film 14 to expose a portion of the substrate 11. When the thickness of the phase layer 12 is set to d1 and the thickness of the protective layer 13 is set to d2, the thickness d1 of the phase layer 12 is thicker than the thickness d2 of the protective layer 13, and the thickness d2 of the protective layer 13 is 15 nm or less.

[0075] exist Figure 3 In step (b), either a positive or negative resist can be used as the resist film material, but a chemically amplified resist for electron beam mapping that can form high-precision patterns is preferred. The thickness of the resist film is, for example, in the range of 50 nm to 250 nm. In particular, when fabricating a phase-shift mask requiring the formation of fine patterns, to prevent pattern collapse, the resist film thickness needs to be thin without increasing the aspect ratio of the resist pattern 16; a thickness of 200 nm or less is preferred. On the other hand, the lower limit of the resist film thickness is determined by comprehensively considering factors such as the etch resistance of the resist material used, and 60 nm or more is preferred. When using a chemically amplified resist film for electron beam mapping, the energy density of the electron beam during mapping is 35 μC / cm². 2 Up to 100 μC / cm 2 Within the range, heat treatment and development treatment are performed after the drawing to obtain the resist pattern 16.

[0076] In addition, Figure 3In step (e), the removal of the resist pattern 16 can be done by wet stripping with a stripping solution or by dry stripping with dry etching.

[0077] In addition, Figure 3 In step (c), the conditions for patterning the light-shielding film 15, which is composed of elemental chromium or chromium compounds, using an oxygen-chlorine dry etching process (Cl / O system) can be known conditions for removing chromium compound films. In addition to chlorine and oxygen, inert gases such as nitrogen and helium can be mixed as needed. The underlying phase-shifting film 14 is resistant to oxygen-chlorine dry etching (Cl / O system) and therefore remains unremoved or unpatterned in this step.

[0078] In addition, Figure 3 In step (d), the fluorine-based dry etching (F-based) conditions for patterning the phase-shifting film 14 can be the known conditions used for dry etching of silicon-based compound films, tantalum compound films, or molybdenum compound films. The fluorine-based gas is typically CF4, C2F6, or SF6, and can be mixed with reactive gases such as oxygen, or inert gases such as nitrogen or helium, as needed. Figure 3 In case (d), the upper light-shielding film 15 or the resist pattern 16 is resistant to fluorine-based dry etching (F-based) and therefore remains unremoved or unpatterned in this process. Figure 3 In (d), the substrate 11 is usually drilled to about 1 nm to 3 nm at the same time to prevent the phase shift film 14 from falling off poorly while performing fine adjustment of the phase difference.

[0079] In addition, Figure 3 In step (f), the conditions for removing the light-shielding film 15 using oxygen-chlorine dry etching (Cl / O system) can be known conditions for removing chromium compound films. In addition to chlorine and oxygen, inert gases such as nitrogen or helium can be mixed as needed. The underlying phase-shifting film 14 and the substrate 11 are both resistant to oxygen-chlorine dry etching (Cl / O system), and therefore are not removed or patterned in this step and remain.

[0080] [Example]

[0081] The embodiments of the present invention will be described in more detail below, but the present invention is not limited to the following embodiments.

[0082] (Example 1)

[0083] A phase layer composed of silicon, molybdenum, oxygen, and nitrogen was deposited on a quartz substrate using a DC sputtering apparatus employing two targets to achieve a thickness of 65 nm. Molybdenum and silicon were used as the targets, and argon, oxygen, and nitrogen were used as the sputtering gases. The composition of the phase layer was analyzed using ESCA, yielding a Si:Mo:O:N ratio of 30:5:20:45 (atomic percentage).

[0084] A protective layer composed of tantalum and oxygen was deposited on the phase layer using a DC sputtering apparatus to a thickness of 8 nm. Tantalum was used as the target, and argon and oxygen were used as the sputtering gases. The composition of the protective layer was analyzed using ESCA, yielding a Ta:O ratio of 30:70 (atomic percentage).

[0085] It should be noted that the phase shift film formed by the phase layer and the protective layer has a transmittance of 6% and a phase difference of 180 degrees.

[0086] Next, a light-shielding film composed of chromium, oxygen, and nitrogen was deposited on the protective layer using a DC sputtering apparatus to a thickness of 50 nm. Chromium was used as the target material, and argon, oxygen, and nitrogen were used as the sputtering gases. The composition of the light-shielding film was analyzed using ESCA, and the result was Cr:O:N = 55:35:10 (atomic percentage).

[0087] Next, a negative chemically amplified electron beam resist was spin-coated onto the light-shielding film with a thickness of 200 nm at a dosage of 35 μC / cm. 2 The resist pattern was formed by electron beam drawing, heat treatment at 110°C for 10 minutes, and paddle development for 90 seconds.

[0088] Next, the light-shielding film was patterned using a dry etching apparatus. The etching gases were chlorine, oxygen, and helium, with a gas pressure set to 5 mTorr, ICP power set to 400 W, and bias power set to 40 W. 100% over-etching was then performed.

[0089] Next, a dry etching apparatus was used to pattern the phase-shifting film, which consisted of a protective layer and a phase layer. The etching gases were CF4 and oxygen, with a gas pressure set to 5 mTorr, ICP power set to 400 W, and bias power set to 40 W. Dry etching was stopped when the quartz substrate had been drilled an average of 3 nm.

[0090] Next, the resist pattern is stripped and cleaned by washing with sulfuric acid and water.

[0091] Next, the light-shielding film was removed using a dry etching apparatus. The etching gases were chlorine, oxygen, and helium, with a gas pressure set to 10 mTorr, ICP power set to 500 W, and bias power set to 10 W. A 200% over-etch was performed. At this point, the underlying phase-shifting film and the quartz substrate remained undamaged.

[0092] Thus, the phase shift mask involved in Example 1 was obtained.

[0093] Next, for this phase-shift mask, the dose of haze generated by accelerated exposure was measured, and the result was 135 kJ / cm². 2 .

[0094] The aforementioned "dose that produces haze by accelerating exposure" means that the higher the value, the more difficult it is to produce haze. If the dose is 70 kJ / cm²... 2 The above addresses any issues with using a phase-shifting mask; if the dose is 100 kJ / cm². 2 The above can be described as phase-shift masks that are extremely difficult to produce haze.

[0095] Based on the above measurement results, it was confirmed that if it is the phase-shift mask of Example 1, the dose is 135 kJ / cm². 2 Therefore, it can reduce the formation of fog.

[0096] (Example 2)

[0097] A phase layer composed of silicon, molybdenum, oxygen, and nitrogen was deposited on a quartz substrate using a DC sputtering apparatus employing two targets to achieve a thickness of 67 nm. Molybdenum and silicon were used as the targets, and argon, oxygen, and nitrogen were used as the sputtering gases. The composition of the phase layer was analyzed using ESCA, yielding a Si:Mo:O:N ratio of 35:5:15:45 (atomic percentage).

[0098] A 5 nm thick protective layer composed of tungsten and oxygen was deposited on the phase layer using a DC sputtering apparatus. Tungsten was used as the target, and argon and oxygen were used as the sputtering gases. The composition of the protective layer was analyzed using ESCA, and the result was W:O = 25:75 (atomic percentage).

[0099] It should be noted that the phase shift film formed by the phase layer and the protective layer has a transmittance of 6% and a phase difference of 180 degrees.

[0100] Next, a light-shielding film composed of chromium, oxygen, and nitrogen was deposited on the protective layer using a DC sputtering apparatus to a thickness of 50 nm. Chromium was used as the target material, and argon, oxygen, and nitrogen were used as the sputtering gases. The composition of the light-shielding film was analyzed using ESCA, and the result was Cr:O:N = 55:35:10 (atomic percentage).

[0101] Next, a negative chemically amplified electron beam resist was spin-coated onto the light-shielding film to a thickness of 200 nm at a dosage of 35 μC / cm. 2 The pattern is drawn with an electron beam, heat-treated at 110°C for 10 minutes, and developed for 90 seconds using a paddle developer, thus forming the resist pattern.

[0102] Next, the light-shielding film was patterned using a dry etching apparatus. The etching gases were chlorine, oxygen, and helium, with a gas pressure set to 5 mTorr, ICP power set to 400 W, and bias power set to 40 W. 100% over-etching was then performed.

[0103] Next, a dry etching apparatus was used to pattern the phase-shifting film, which consisted of a protective layer and a phase layer. The etching gases were CF4 and oxygen, with a gas pressure set to 5 mTorr, ICP power set to 400 W, and bias power set to 40 W. Dry etching was stopped when the quartz substrate had been drilled an average of 3 nm.

[0104] Next, the resist pattern is stripped and cleaned by washing with sulfuric acid and water.

[0105] Next, the light-shielding film was removed using a dry etching apparatus. The etching gases were chlorine, oxygen, and helium, with a gas pressure set to 10 mTorr, ICP power set to 500 W, and bias power set to 10 W. A 200% over-etch was performed. At this point, the underlying phase-shifting film and the quartz substrate remained undamaged.

[0106] Thus, the phase-shift mask involved in Example 2 was obtained.

[0107] Next, for this phase-shift mask, the dose of haze generated by accelerated exposure was measured, and the result was 92 kJ / cm². 2 .

[0108] Based on the above results, it was confirmed that if it is the phase-shift mask of Example 2, the dose is 92 kJ / cm². 2 Therefore, it can reduce the formation of fog.

[0109] (Example 3)

[0110] A phase layer composed of silicon, molybdenum, oxygen, and nitrogen was deposited on a quartz substrate using a DC sputtering apparatus employing two targets to achieve a thickness of 67 nm. Molybdenum and silicon were used as the targets, and argon, oxygen, and nitrogen were used as the sputtering gases. The composition of the phase layer was analyzed using ESCA, yielding a Si:Mo:O:N ratio of 40:8:7:45 (atomic percentage).

[0111] A protective layer composed of tellurium and oxygen was deposited on the phase layer using a DC sputtering apparatus to a thickness of 3 nm. Tellurium was used as the target material, and argon and oxygen were used as the sputtering gases. The composition of the protective layer was analyzed using ESCA, and the result was Te:O = 35:65 (atomic percentage).

[0112] It should be noted that the phase shift film formed by the phase layer and the protective layer has a transmittance of 6% and a phase difference of 180 degrees.

[0113] Next, a light-shielding film composed of chromium, oxygen, and nitrogen was deposited on the protective layer using a DC sputtering apparatus to a thickness of 50 nm. Chromium was used as the target material, and argon, oxygen, and nitrogen were used as the sputtering gases. The composition of the light-shielding film was analyzed using ESCA, and the result was Cr:O:N = 55:35:10 (atomic percentage).

[0114] Next, a negative chemically amplified electron beam resist was spin-coated onto the light-shielding film to a thickness of 200 nm at a dosage of 35 μC / cm. 2 The pattern is drawn with an electron beam, heat-treated at 110°C for 10 minutes, and developed for 90 seconds using a paddle developer, thus forming the resist pattern.

[0115] Next, the light-shielding film was patterned using a dry etching apparatus. The etching gases were chlorine, oxygen, and helium, with a gas pressure set to 5 mTorr, ICP power set to 400 W, and bias power set to 40 W. 100% over-etching was then performed.

[0116] Next, a dry etching apparatus was used to pattern the phase-shifting film, which consists of a protective layer and a phase layer. The etching gases used were CF4 and oxygen, with the gas pressure set to 5 mTorr, the ICP power set to 400 W, and the bias power set to 40 W. Dry etching was stopped when the quartz substrate had been drilled an average of 3 nm.

[0117] Next, the resist pattern is stripped and cleaned by washing with sulfuric acid and water.

[0118] Next, the light-shielding film was removed using a dry etching apparatus. The etching gases were chlorine, oxygen, and helium, with a gas pressure set to 10 mTorr, ICP power set to 500 W, and bias power set to 10 W. A 200% over-etch was performed. At this point, the underlying phase-shifting film and the quartz substrate remained undamaged.

[0119] This yields the phase-shift mask involved in Example 3.

[0120] Next, for this phase-shift mask, the dose of haze generated by accelerated exposure was measured, and the result was 87 kJ / cm². 2 .

[0121] Based on the above results, it was confirmed that if it is the phase-shift mask of Example 3, the dose is 87 kJ / cm². 2 Therefore, it can reduce the formation of fog.

[0122] (Example 4)

[0123] A phase layer composed of silicon, molybdenum, oxygen, and nitrogen was deposited on a quartz substrate using a DC sputtering apparatus employing two targets to achieve a thickness of 70 nm. Molybdenum and silicon were used as the targets, and argon, oxygen, and nitrogen were used as the sputtering gases. The composition of the phase layer was analyzed using ESCA, yielding a Si:Mo:O:N ratio of 35:5:15:45 (atomic percentage).

[0124] A protective layer composed of tantalum, oxygen, and nitrogen was deposited on the phase layer using a DC sputtering apparatus to a thickness of 2 nm. Tantalum was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gases. The composition of the protective layer was analyzed using ESCA, yielding a Ta:O:N ratio of 65:5:30 (atomic percentage).

[0125] It should be noted that the phase shift film formed by the phase layer and the protective layer has a transmittance of 6% and a phase difference of 180 degrees.

[0126] Next, a light-shielding film composed of chromium, oxygen, and nitrogen was deposited on the protective layer using a DC sputtering apparatus to a thickness of 50 nm. Chromium was used as the target material, and argon, oxygen, and nitrogen were used as the sputtering gases. The composition of the light-shielding film was analyzed using ESCA, and the result was Cr:O:N = 55:35:10 (atomic percentage).

[0127] Next, a negative chemically amplified electron beam resist was spin-coated onto the light-shielding film to a thickness of 200 nm at a dosage of 35 μC / cm. 2 The pattern is drawn with an electron beam, heat-treated at 110°C for 10 minutes, and developed for 90 seconds using a paddle developer, thus forming the resist pattern.

[0128] Next, the light-shielding film was patterned using a dry etching apparatus. The etching gases used were chlorine, oxygen, and helium, with the gas pressure set to 5 mTorr, ICP power set to 400 W, and bias power set to 40 W. 100% over-etching was then performed.

[0129] Next, a dry etching apparatus was used to pattern the phase-shifting film, which consisted of a protective layer and a phase layer. The etching gases were CF4 and oxygen, with a gas pressure set to 5 mTorr, ICP power set to 400 W, and bias power set to 40 W. Dry etching was stopped when the quartz substrate had been drilled an average of 3 nm.

[0130] Next, the resist pattern is stripped and cleaned by washing with sulfuric acid and water.

[0131] Next, the light-shielding film was removed using a dry etching apparatus. The etching gases were chlorine, oxygen, and helium, with a gas pressure set to 10 mTorr, ICP power set to 500 W, and bias power set to 10 W. A 200% over-etch was performed. At this point, the underlying phase-shifting film and the quartz substrate remained undamaged.

[0132] This yields the phase-shift mask involved in Example 4.

[0133] Next, for this phase-shift mask, the dose of haze generated by accelerated exposure was measured, and the result was 110 kJ / cm². 2 .

[0134] Based on the above results, it was confirmed that if it is the phase-shift mask of Example 4, the dose is 110 kJ / cm². 2 Therefore, it can reduce the formation of fog.

[0135] (Comparative Example 1)

[0136] A phase layer composed of silicon, molybdenum, oxygen, and nitrogen was deposited on a quartz substrate using a DC sputtering apparatus employing two targets to achieve a thickness of 70 nm. Molybdenum and silicon were used as the targets, and argon, oxygen, and nitrogen were used as the sputtering gases. The composition of the phase layer was analyzed using ESCA, yielding a Si:Mo:O:N ratio of 40:8:7:45 (atomic percentage).

[0137] Next, a light-shielding film composed of chromium, oxygen, and nitrogen was deposited on the phase layer using a DC sputtering apparatus to a thickness of 50 nm. Chromium was used as the target material, and argon, oxygen, and nitrogen were used as the sputtering gases. The composition of the light-shielding film was analyzed using ESCA, and the result was Cr:O:N = 55:35:10 (atomic percentage).

[0138] Next, a negative chemically amplified electron beam resist was spin-coated onto the light-shielding film with a thickness of 200 nm at a dosage of 35 μC / cm. 2 The pattern is drawn with an electron beam, heat-treated at 110°C for 10 minutes, and developed for 90 seconds using a paddle developer, thus forming the resist pattern.

[0139] Next, the light-shielding film was patterned using a dry etching apparatus. The etching gases were chlorine, oxygen, and helium, with a gas pressure set to 5 mTorr, ICP power set to 400 W, and bias power set to 40 W. 100% over-etching was then performed.

[0140] Next, a dry etching apparatus was used to pattern the phase-shifting film, which consisted only of the phase layer. The etching gases were CF4 and oxygen, with a gas pressure set to 5 mTorr, ICP power set to 400 W, and bias power set to 40 W. Dry etching was stopped when the quartz substrate had been drilled an average of 3 nm.

[0141] Next, the resist pattern is stripped and cleaned by washing with sulfuric acid and water.

[0142] Next, the light-shielding film was removed using a dry etching apparatus. The etching gases were chlorine, oxygen, and helium, with a gas pressure set to 10 mTorr, ICP power set to 500 W, and bias power set to 10 W. A 200% over-etch was performed. At this point, the underlying phase-shifting film and the quartz substrate remained undamaged.

[0143] Thus, the phase shift mask involved in Comparative Example 1 was obtained. That is, the phase shift mask involved in Comparative Example 1 is a phase shift mask without the protective layer formed in Examples 1 to 4.

[0144] Next, for this phase-shift mask, the dose of haze generated by accelerated exposure was measured, and the result was 58 kJ / cm². 2 .

[0145] Based on the above results, it was confirmed that the dose was 58 kJ / cm in the phase-shift mask of Comparative Example 1. 2 Therefore, it cannot sufficiently reduce the generation of fog.

[0146] As mentioned above, it is known that forming a protective layer on the phase layer is effective in reducing the amount of haze generated by the phase shift mask.

[0147] The phase-shifting mask blank and the phase-shifting mask made using the above embodiments have been described. However, the above embodiments are merely examples for implementing the present invention, and the present invention is not limited thereto. Furthermore, modifications to these embodiments are within the scope of the present invention, and it should be understood that various other embodiments can be implemented within the scope of the present invention.

[0148] Industrial applicability

[0149] In this invention, by selecting the composition, film thickness and layer structure of the phase shift mask blank, as well as the manufacturing process and conditions of the phase shift mask using the phase shift mask blank within an appropriate range, a phase shift mask that forms a fine pattern corresponding to the manufacturing of logic devices below 28nm or memory devices below 30nm can be provided with high precision.

[0150] Explanation of symbols

[0151] 10. Phase Shift Mask Blank

[0152] 11. For substrates (substrates) with a transparent exposure wavelength.

[0153] 12. Phase Layer (Phase Difference Transmittance Adjustment Layer)

[0154] 13··· Protective Layer (Gas Permeates Protective Layer)

[0155] 14. Phase Shifting Film

[0156] 15···Light-shielding film

[0157] 16···Resist Pattern

[0158] 17. Phase Shift Film Pattern

[0159] 100··· Phase Shift Mask

[0160] d1··· Phase layer thickness

[0161] d2··· Protective layer film thickness

Claims

1. A phase-shifting mask blank, used for fabricating a phase-shifting mask suitable for exposure light with wavelengths below 200 nm, characterized in that, It comprises a transparent substrate and a phase-shifting film formed on the transparent substrate. The phase-shifting film comprises: a phase difference transmittance adjustment layer capable of adjusting the phase and transmittance of transmitted exposure light by predetermined amounts; and a gas permeability protection layer formed on the phase difference transmittance adjustment layer to prevent oxygen-containing gas from permeating into the phase difference transmittance adjustment layer, wherein the oxygen-containing molecules include water molecules. The phase difference transmittance adjustment layer is located on the transparent substrate side and contains silicon, a transition metal, oxygen, and nitrogen. The transition metal includes molybdenum. The gas permeability protective layer contains at least one material selected from tantalum oxide, tantalum oxynitride, tungsten oxide, and tellurium oxide. When the thickness of the phase difference transmittance adjustment layer is set to d1 and the thickness of the gas permeation protection layer is set to d2, d1 is greater than d2, and d2 is greater than 2nm and less than 8nm.

2. The phase-shifting mask blank according to claim 1, characterized in that, The phase-shifting film is resistant to oxychlorine-based etching (Cl / O-based) and can be etched using fluorine-based etching (F-based).

3. The phase-shifting mask blank according to claim 1 or claim 2, characterized in that, The transition metal also includes at least one selected from titanium, vanadium, cobalt, nickel, zirconium, niobium, and hafnium.

4. A phase-shifting mask, which is a phase-shifting mask with a circuit pattern suitable for exposure light with wavelengths below 200 nm, characterized in that, It comprises a transparent substrate and a phase-shifting film formed on the transparent substrate. The phase-shifting film comprises: a phase difference transmittance adjustment layer capable of adjusting the phase and transmittance of transmitted exposure light by predetermined amounts; and a gas permeability protection layer formed on the phase difference transmittance adjustment layer to prevent oxygen-containing gas from permeating into the phase difference transmittance adjustment layer, wherein the oxygen-containing molecules include water molecules. The phase difference transmittance adjustment layer is located on the transparent substrate side and contains silicon, a transition metal, oxygen, and nitrogen. The transition metal includes molybdenum. The gas permeability protective layer contains at least one material selected from tantalum oxide, tantalum oxynitride, tungsten oxide, and tellurium oxide. When the thickness of the phase difference transmittance adjustment layer is set to d1 and the thickness of the gas permeation protection layer is set to d2, d1 is greater than d2, and d2 is greater than 2nm and less than 8nm.

5. The phase-shifting mask according to claim 4, characterized in that, The phase-shifting film is resistant to oxychlorine-based etching (Cl / O-based) and can be etched using fluorine-based etching (F-based).

6. The phase-shifting mask according to claim 4 or claim 5, characterized in that, The transition metal also includes at least one selected from titanium, vanadium, cobalt, nickel, zirconium, niobium, and hafnium.

7. A method for manufacturing a phase shift mask, comprising a method for manufacturing a phase shift mask using a phase shift mask blank according to any one of claims 1 to 3, characterized in that, include: The process of forming a light-shielding film on the phase-shifting film; The process of forming a resist pattern on the light-shielding film formed on the phase-shifting film; The process of forming the pattern on the light-shielding film by using an oxygen-chlorine etchant (Cl / O system) after the resist pattern is formed; After forming a pattern on the light-shielding film, a process of forming a pattern on the phase-shifting film using fluorine-based etching (F-based); The process of removing the resist pattern after forming a pattern on the phase-shifting film; and The process of removing the light-shielding film from the phase-shifting film by using an oxygen-chlorine etchant (Cl / O) after removing the resist pattern.

Citation Information

Patent Citations

  • Method of manufacturing photomask blank, photomask blank, method of manufacturing photomask, photomask, and photomask metal target

    JP2018173621A

  • Photomask blank manufacturing method and photomask manufacturing method

    US20100167185A1

  • Blankmask and photomask using the same

    US20150268552A1

  • Mask blank, phase shift mask and method for manufacturing semiconductor device

    US20180252995A1

  • A patterning device and method of use thereof

    WO2020160851A1